Implementasi Penegakan Hukum terhadap Pelaku Tindak Pidana Pajak Pertambahan Nilai (PPN) dalam Upaya Mengembalikan Pendapatan Negara Berdasarkan Undang-Undang Nomor 6 Tahun 1983 tentang Ketentuan Umum dan Tata Cara Perpajakan (KUP) - Mulia, Sari Dapot (Jurnal Ragam Pengabdian, 2024)
Taxes are the main source of Indonesian state revenue, and Indonesia has significant tax revenue potential due to its large population. However, this potential does not rule out the possibility of criminal tax violations, such as Value Added Tax (VAT) crimes. This study examines Decision Number: 1263/Pid.B/2019/PN_Jkt.PST. The research was conducted using normative juridical methods with bibliographical data from books, journals, laws and regulations, and tax expert theories. Based on qualitative normative analysis, the findings indicate that the judge's decision does not fulfill a sense of justice. The court imposed fines that are inconsistent with Law No. 6 of 1983 on General Provisions and Tax Procedures (KUP), even though the prosecution was linked to a special law on tax crimes (Lex Specialis Derogat). The judge's decision in this case demonstrates that criminal sanctions for tax violations remain lenient and do not provide a deterrent effect for perpetrators. This leniency is particularly concerning given that tax crimes are categorized as extraordinary crimes that cause significant harm to state revenue. Such judicial phenomena remain common in current tax criminal sanction decisions, indicating that law enforcement in the tax sector still requires substantial improvement to ensure justice and optimal recovery of state financial losses.